The influence of body mass index (BMI) and physical activity changes on the effectiveness of e-health in obesity among adults: A systematic review - Mahmuddin, Mahmuddin; Mulyono, Sigit; Rekawati, Etty; Wiarsih, Wiwin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: The use of e-health is now widely used as a new intervention e-health can be applications in smart phones, smart watches, or wearables, as well as telemedicine, interactive video and web-based interventions. Purpose: Submitting the results of exploration related to the impact of e-health use in increasing physical activity and changes in BMI in adults with obesity. Method: Literature reviews on several databases such as clinical key nursing, sage journal, and Pubmed using PRISMA methods. Results: This systematic review study proves that eHealth has an influence on physical activity and BMI in adults with obesity. From the 7 articles that used e-health as an intervention in changing physical activity and BMI showed significant results against changes in physical activity, BMI despite using different types of eHealth, such as virtual reality, smartphone applications/wearable devices and telehealth. Conclusion: The use of e-health can be recommended as part of a body weight management strategy as it has a good impact over time and needs to be integrated with nursing interventions so that nurses can monitor patient progress and adjust recommendations based on the data collected.